Charting Directions for Research on Immigrant Children Affected by Undocumented Status. (November 2017) - Zayas, Luis H.; Brabeck, Kalina M.; Heffron, Laurie Cook; Dreby, Joanna; Calzada, Esther J.; Parra-Cardona, J. Rubén; Dettlaff, Alan J.; Heidbrink, Lauren; Perreira, Krista M.; Yoshikawa, Hirokazu
Three groups of children from Mexico and Central America are vulnerable to effects of U.S. immigration policies: (1) foreign-born children who entered the United States with undocumented immigrant parents; (2) unaccompanied children who entered the United States alone; and (3) U.S.-born citizen-children of undocumented immigrant parents. Despite the recent demographic growth of these youth, scholarship on their strengths and challenges is under-theorized and isolated within specific disciplines. Hence, service providers, researchers, and policymakers have insufficient research to inform their efforts to support the children's well-being. A group of scholars and service providers with expertise in immigrant children convened to establish consensus areas and identify gaps in knowledge of undocumented, unaccompanied, and citizen-children of undocumented immigrant parents. The primary goal was to establish a research agenda that increases interdisciplinary collaborations, informs clinical practice, and influences policies. This report summarizes key issues and recommendations that emerged from the meeting.